Capgras Syndrome in Dementia: A Systematic Review of Case Studies - Margariti, Charikleia; Mircea, Margareta-Theodora (Current Alzheimer Research, 2024)
BackgroundIn an ageing population, dementia has become an imminent healthcare emergency. Capgras syndrome, the most common delusion of misidentification (DMS), is frequently found alongside dementia. Previous research showed that Capgras syndrome has significant negative effects on people living with dementia and their carers due to its complex presentation and impact on their lives. This qualitative systematic review explores the evidence base of the effective management and treatment of Capgras syndrome in dementia.AimsAs per our knowledge, this is the first systematic review exploring the symptomatology of Capgras syndrome across different types of dementia. Additionally, it aims to identify the treatments used and their efficacy.MethodsFour databases (EMBASE, MEDLINE, PsycINFO, and CINHAL) were screened in March, 2023. Twenty-six studies met the inclusion criteria and were included in the review. Thematic analysis was performed to explore and synthesise the qualitative findings of the studies.ResultsThree conceptual themes were identified: diagnostic tools, Capgras syndrome symptomatology, and Capgras syndrome treatment. Results showed that Capgras syndrome in dementia is not diagnosed and treated in a standardised manner. Following the pharmacological intervention, 28% of cases showed resolution of symptoms, and another 28% experienced improvement. However, 7% of cases reported worsening symptoms, and 10.7% experienced no change. While some patients had positive outcomes with specific medications, others either did not respond or experienced a deterioration of their condition.ConclusionThe results highlight that there is no single treatment approach for Capgras syndrome in people living with dementia. This underscores the need for person-centred care, where treatment is tailored to individual needs. The review also reveals a heavy reliance on antipsychotic medications and a noticeable lack of psychosocial interventions. Given the limited benefits and significant risks associated with antipsychotics, future research should prioritise developing and testing psychosocial approaches. Additionally, establishing standardised diagnostic criteria and consistent outcome measures for Capgras syndrome in dementia is crucial for evaluating treatment effectiveness and improving care.
Keywords: dementia